2012
DOI: 10.1017/s0033291712000864
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric in-patient care and suicide in England, 1997 to 2008: a longitudinal study

Abstract: The rate of suicide among psychiatric in-patients in England has fallen considerably. Possible explanations include falling general population rates, changes in the at-risk population or improved in-patient safety. However, a transfer of risk to the period after discharge or other clinical settings such as crisis resolution teams cannot be ruled out.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 25 publications
4
44
0
2
Order By: Relevance
“…Because prisoners who self-harm usually have several psychiatric comorbidities and psychosocial difficulties, 34,35 interventions might need to be more complex than in the general community, be multidisciplinary, and include speciality input. Restriction of access to means for self-harm is also important, similar to suicide prevention in psychiatric inpatients 36 . Overall, our findings are consistent with calls for greater health-care involvement in the management and prevention of self-harm in prisons 37 .…”
Section: Discussionsupporting
confidence: 82%
“…Because prisoners who self-harm usually have several psychiatric comorbidities and psychosocial difficulties, 34,35 interventions might need to be more complex than in the general community, be multidisciplinary, and include speciality input. Restriction of access to means for self-harm is also important, similar to suicide prevention in psychiatric inpatients 36 . Overall, our findings are consistent with calls for greater health-care involvement in the management and prevention of self-harm in prisons 37 .…”
Section: Discussionsupporting
confidence: 82%
“…The rate of suicide has been reported at five per 1000 occupied beds each year. 19 A meta-analysis of 27 studies reported a rate of 147 suicides per 100 000 inpatient years, with individual studies reporting figures as high as 860 suicides per 100 000 inpatient years. 20 Suicide tends to occur early .…”
Section: Inpatients and Recent Dischargementioning
confidence: 99%
“…While Walsh et al [14] noted in their meta-analyses that previous studies found lower suicide rates than more recent studies, only few studies have actually addressed the period effects of inpatient suicide rates. Large cohort studies from England, Israel, and Denmark have reported a significant decreasing trend in inpatient suicide rates from the late 1990s into the new millennium [49,50,51]. The English study found that the decrease was highest in the youngest age group (15–44 years) and among patients with schizophrenia, whereas the Danish study noted that the decrease was most pronounced among female patients.…”
Section: Prevalence Rates and Time Change Of Inpatient Suicidementioning
confidence: 99%
“…Both studies found that the suicide rate had changed among those patients recently discharged. In England, the rate of post-discharge suicide rose from 1.39 per 1000 discharges in 1997/98 to 1.66 per 1000 discharges in 2007/08 [50], whereas, in Denmark, the post-discharge suicide rate was found to have decreased [52]. …”
Section: Prevalence Rates and Time Change Of Inpatient Suicidementioning
confidence: 99%